Nonsense-mediated mRNA decay factors act in concert to regulate common mRNA targets. - Rehwinkel, J.; Letunic, I.; Raes, J.; Bork, P.; Izaurralde, E. (RNA (New York, N.Y.), 2005)
Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that degrades mRNAs containing nonsense codons, and regulates the expression of naturally occurring transcripts. While NMD is not essential in yeast or nematodes, UPF1, a key NMD effector, is essential in mice. Here we show that NMD components are required for cell proliferation in Drosophila. This raises the question of whether NMD effectors diverged functionally during evolution. To address this question, we examined expression profiles in Drosophila cells depleted of all known metazoan NMD components. We show that UPF1, UPF2, UPF3, SMG1, SMG5, and SMG6 regulate in concert the expression of a cohort of genes with functions in a wide range of cellular activities, including cell cycle progression. Only a few transcripts were regulated exclusively by individual factors, suggesting that these proteins act mainly in the NMD pathway and their role in mRNA decay has not diverged substantially. Finally, the vast majority of NMD targets in Drosophila are not orthologs of targets previously identified in yeast or human cells. Thus phenotypic differences observed across species following inhibition of NMD can be largely attributed to changes in the repertoire of regulated genes.